Effect of ultrasound and additives treatment as mitigation strategies to reduce acrylamide formation in potato crisps on industrial scale - Bruno, Francesca; Ledbetter, Moira; Davies, Ben; Riedinger, Lena; Blidi, Slim; Sturrock, Keith; McNamara, Ged; Montague, Gary; Fiore, Alberto (Lwt-Food Science and Technology, 2024)
The aim of this work was to examine the applicability on large scale of additives and ultrasound treatments during soaking of potatoes before frying to mitigate the formation of acrylamide in potato crisps. Calcium chloride and citric acid were applied at laboratory scale in various concentrations and orders during washing before frying, to establish optimum conditions which were scaled up to pilot plant. Up to 91.0% reduction in acrylamide was obtained at laboratory scale. Both concentration and order of additives influenced the extent of the mitigation observed, with a higher concentration of additive in the second wash being beneficial. When upscaled to factory pilot plant, the reduction observed was not consistent across the three trials, with a 33.4% reduction in the first trial but no significant reduction in following studies. A 2-min ultrasound treatment was applied in two trials to test various powers and amplitudes, and washing combinations respectively. Up to 67.1% of acrylamide reduction was recorded after 2 min of ultrasound treatment in the cold wash followed by hot wash; however, ultrasound treatment was not effective in reducing acrylamide or its precursors when solely applied or when followed by cold wash under the tested conditions of duration and power.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Acrylamide; Additives; Blanching; Potato crisps; ultrasound